Displacement of Dental Implant Into the Submental Space After Surgical Integration - Kirtay, Mustafa; Yolcu, Umit; Dundar, Serkan (Lippincott Williams & Wilkins, 2017)
Osseointegrated dental implants are common and widely used to treat edentulism. Implant displacement into the maxillofacial spaces during surgery or after a period of use is a complication recognized in the literature. Foreign objects such as titanium dental implants in the maxillofacial region must be removed because they cause infection due to tissue reaction. In this report, the authors present the case of a patient whose dental implant slipped into the submental space after surgical integration and describe the surgical removal of the implant via an extraoral approach.
Keywords: Dental implant migration; submental incision; submental space